Neuromuscular fatigue in hamstring and quadriceps muscles after simulated soccer match play and typical training sessions - Massamba, A; Kouzkouz, N; Geny, B; Favret, F; Hureau, T. (Medicine & Science in Sports & Exercise, 2025)
Purpose This study investigated the mechanisms of neuromuscular fatigue and recovery in quadriceps and hamstring muscles after soccer match play and typical training sessions dedicated to the physical development of players.